Sintesis Membran Selulosa Asetat Untuk Desalinasi Air Payau - Vany Silvia; Jhon Armedi Pinem; Rozanna Sri Irianty (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
One of energy that can be used to produce pure water in coastal areas of Riau is using cellulose acetate membrane. Raw material used in this experiment is a cellulose acetate, acetone and formamide. This research aims to make cellulose acetate membrane for brackish water treatment process into pure water with cellulose acetate variations of 16%,17%,18%,19% and 20% and operating pressure is 2, 4, 6, 8 and 10 bar. The results obtained are greater then the composition of the cellulose acetate will be smaller flux produced and greater the rejection is generated. The greater the operating pressure, the greater the flux obtained and smaller the rejection obtained.Keywords : cellulose acetate, flux, membrane,rejection